2021
DOI: 10.1108/tqm-10-2020-0227
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi-item Operational Excellence scale: Exploratory and confirmatory factor analysis

Abstract: PurposeConsidering the relevance of operational excellence as a business strategy, organizations are striving to improve themselves by adopting best practices and universally accepted principles through the process of continuous improvement, and these principles should be embedded in the culture of an organization. Organizations pursue to align themselves by continuously improving their processes by adopting scientifically proven techniques and cultural transformation throughout the organization. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The results of the EFA indicated that the sample size was adequate, because the KMO was 0.651. According to the rule of thumb, a KMO between 0.6 to 1 indicates that a sample is adequate, while a KMO below 0.6 shows that the sample is inadequate and that remedial action is required (Wahyudi, Sulistiani, & Muhajat, 2019;Saeed, Tasmin, Mahmood, & Hafeez, 2021). Also, the total variance explained was 58%, indicating a strong strength of association and that a better prediction can be made using the data obtained (Shirk & Karver, 2003).…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…The results of the EFA indicated that the sample size was adequate, because the KMO was 0.651. According to the rule of thumb, a KMO between 0.6 to 1 indicates that a sample is adequate, while a KMO below 0.6 shows that the sample is inadequate and that remedial action is required (Wahyudi, Sulistiani, & Muhajat, 2019;Saeed, Tasmin, Mahmood, & Hafeez, 2021). Also, the total variance explained was 58%, indicating a strong strength of association and that a better prediction can be made using the data obtained (Shirk & Karver, 2003).…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…In the operational excellence field, empirical and conceptual papers abound. However, review papers that systematically explored what exists in the operational excellence body of literature, its research gaps and future research directions are very few (Saeed et al, 2021). Thus, the current study attempted first to examine what exists in the operational excellence body of literature, second to explore the research gaps, and thirdly to identify future research directions in the operational excellence context.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2009 was taken as the beginning year of the current SLR, given that from 2009 onwards, the number of operational excellence research studies have significantly increased (Saeed et al, 2021). The literature search was based on terms such as operational excellence, operational excellence research in Sri Lanka, factors that affect operational excellence, and gaps in operational excellence research.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of partners can be a solution. Through the Baldrige criteria, finding the right partner needs to be done by the organization in its efforts to develop the organization and its wider expansion (Saeed et al, 2022).…”
Section: Focus On the Market And Customersmentioning
confidence: 99%